The Space Density of Magnetic and Non-magnetic Cataclysmic Variables, and Implications for CV Evolution - M. L. Pretorius (Acta Polytechnica CTU Proceedings)
We present constraints on the space densities of non-magnetic and magnetic cataclysmic variables, and discuss some implications for models of the evolution of CVs. The high predicted non-magnetic CV space density is only consistent with observations if the majority of these systems are extremely faint in X-rays. The data cannot rule out the very simple model where long-period IPs evolve into polars and account for the entire short-period polar population. The fraction of WDs that are strongly magnetic is not significantly higher for CV primaries than for isolated WDs. Finally, the space density of IPs is high enough to explain the bright, hard X-ray source population seen in the Galactic Centre.